Attitudes towards mental health and the integration of mental health services into primary health care: a cross-sectional survey among health-care workers in Lvea Em District, Cambodia - Maria Alfredsson; Miguel San Sebastian; Bhoomikumar Jeghannathan (Taylor & Francis Group, 2017)
Background: Cambodia is a country where the resources for treating mental health disorders are far from sufficient. One strategy to narrow the treatment gap is to integrate mental health into primary health care (PHC). Understanding the knowledge and attitudes towards mental health integration that health-care workers have is important for assessing the challenges and opportunities when planning a potential integration project. Objective: The aim of this study was to assess these basic conditions in Lvea Em District, Cambodia. Design: A structured self-reporting questionnaire regarding attitudes and knowledge about mental health and its integration into PHC was collected from 75 health-care workers in Lvea Em District, Cambodia in October 2015. Firstly, descriptive analyses were carried out, and secondly, linear regression analyses to assess the relationship between attitudes and socio-demographic variables were conducted. Results: There was clear support towards integrating mental health services into PHC among these participants as 81.3% were interested in personally delivering mental health care at their units. Respondents who reported having received some kind of mental health-care training tended to have a more positive attitude towards mentally ill people (p = 0.005) and those who thought there was a high need for mental health care had a more favourable attitude towards the integration of mental health services (p = 0.007). Conclusions: The most important finding from this survey was the willingness and the acceptance of the need for integration of mental health care. This enhances the feasibility of integrating mental health services at the PHC level. Improving the competence of mental health care in these settings will likely help to reduce the treatment gap for mental, neurological and substance use disorders in Cambodia.